On δ-Small Projective Modules - Al-Mothafar, Nuhad; Yassin, Sahira (Iraqi Journal of Science, 2024)
Let be a commutative ring with unity and let be a non-zero unitary module. Inthis work we present a -small projective module concept as a generalization of smallprojective. Also we generalize some properties of small epimorphism to δ-smallepimorphism. We also introduce the notation of δ-small hereditary modules and δ-smallprojective covers.